Role of Magnetic Resonance Imaging in Characterization and Management of Uterine Leiomyoma - Mahmood, Surala Qadr; Mahmood, Kawa Abdulla; Muhamad, Nyan Mustafa (Sulaimani Journal for Pure and Applied Sciences, 2023)
Background: The most frequent benign disease affecting women of reproductive age is uterine leiomyoma. Magnetic Resonance Imaging (MRI) is the current state of art imaging modality for localization and characterization. Objective: To determine the relevance of MRI in the Characterization and management of leiomyoma and to analyze clinical practice advantages of MRI findings. Patients and Methods: This study included 50 individuals with uterine fibroids detected By trans-abdominal or transvaginal US. MRI was done to confirm, characterize and pinpoint their exact location and any abnormal characterization. Results: There was a significant (p≤0.05) association between the impression of fibroid (non-degenerated, degenerated leiomyoma), postgadolinium enhancement of fibroid and histopathological findings. There was no significant relationship between MRI (T1-weighted image) results, and MRI (T2- weighted image), their histological findings, and management. Conclusions: leiomyomas can provide a standard signal during MR imaging, but larger tumour may display a variety of degeneration patterns that significantly alter the look of the lesion. MRI provide better fibroid characterization, helps differentiate degenerated from nondegenerated leiomyoma and guides in choosing safe and better management procedure.
Keywords: Contrast; degeneration; enhancement; heterogeneous; homogenous; leiomyoma; MRI